LANGUAGE ANXIETY AMONG INTERNATIONAL STUDENTS: A CASE STUDY OF IELTS CANDIDATES IN A PRIVATE UNIVERSITY - Mariam Mohammed; Aini Syahira Jamaluddin (Jurnal Penyelidikan Sains Sosial, 2023)
This study aims to better understand language anxiety among international students. Its goal is to convey the stress that international students experience when learning English, especially in preparation for the IELTS exam. Additionally, it is to observe how students handle and overcome strain and worry when getting ready for the IELTS exam. International students' actual experiences at Albukhary International University served as the basis for this study. Eight students from different countries were interviewed to understand in-depth their experiences in studying for IELTS. The respondents were questioned about how they prepared for the IELTS exam, the difficulties they encountered, how they dealt with their language anxieties, and their experiences while getting ready for the test.